Pendugaan Parameter Demografi dan Bentuk Sebaran Spasial Biawak Komodo di Pulau Rinca, Taman Nasional Komodo - Yanto Santosa; Raden Yosi Zainal Muhammad; Dede Aulia Rahman (Jurnal Ilmu Pertanian Indonesia, 2012)
Komodo is one of the protected rare reptiles that can only be found within the Komodo National Park and the northern island of Flores. This study was aimed to determine the species population parameters and spatial distribution. Data collection on population and spatial distribution of komodo were conducted using 20 transects with four repetitions, of which 5 transects were placed in the deciduous forest and 15 in the savannah with a total sampling area of 200 ha. The form of spatial distribution was obtained using the methods of variance ratio, dispersion index, green index, clumping index and chi-square. In addition, vegetation analysis was carried out on a 4 ha sampling plot. Results of the observations indicated that the size of the komodo population on Rinca Island was 698 individuals with a density of 3.15 individuals/km2 comprised of: adults with 1.7 individuals/km2, sub-adults with 0.65 individuals/km2, juveniles with 0.8 individuals/km2 and infants with 0.4 individuals/km2. The density of komodo in the deciduous forest (8.4 individuals/km2) was much higher than in the savannah (0.64 individuals/km2). The birth rate of komodo (11.27%) was higher than the mortality rate (4.23%). The sex ratio was 3 : 1. Within the study area, komodo distributed within clusters as indicated by the ratio of mean value of 3.77; dispersion index 3.72; green index 0.08, clumping index 2.72 and chi-square 167.059.6. Chance of encounters with Komodo in both types of habitat was much higher in the morning (80%) than during the day (20%). To increase the population size, the manager should intervene with the maintenance of hatchlings to acquire low mortality rate and protection of komodo’s natural prey species.